Index Penulis - Index Penulis TIP (Department of Agroindustrial Technology, Bogor Agricultural University, 2014)
INDEKS PENULIS VOLUME 24 Aman, W.P. 137 Anandito, R.B.K. 53 Andarwulan, N. 209 Andasuryani 43 Aryanto, A.Y. 97 Bahmid, N.A. 226 Bantacut, T. 105 Budiastra, I.W. 43 Damanyanthi, E. 28 Darmanto, W. 105 Daryanto, A. 114 Dwiyanti, H. 28 Dwiyono, K. 179 Eriyatno 34 Fahma, F. 125 Fahrizal 189 Gumbira-Sa’id, E. 11, 114, 157 Haditjaroko, L. 20, 179 Hariyadi, P. 209 Hasan, M.F. 114 Hasanudin, U. 11 Hendra 82 Herdiyeni, Y. 82 Hermawan, D. 125 Indrasti, N.S. 97, 243 Ismayana, A. 243 Jading, A. 137 Jaya, R. 61 Kartika, I.A. 125 Ketaren, S. 148 Khasanah, L.U. 53 Kurniati, M. 125 Kusmana, C. 200 Kustiyo, A. 1 Lubis, M.R.R. 72 Machfud 34, 61, 157 Maddu, A. 226, 243 Mangunwidjaja, Dj. 218 Manurung, A.J. 20 Marimin 61, 82, 189 Meryandini, A. 20 Mu’tamar, M.F.F. 34 Pari, G. 157 Payung, P. 137 Purnomo, E.H. 209 Purwanto, M.Y.J. 189 Purwanto, Y.A. 43 Raharja, S. 61, 251 Richana, N. 218 Rimbawan 28 Riyadi, H. 28 Romli, M. 97 Rosmeika 235 Sarono 11 Sartika, N.D. 157 Sarungallo, Z.L. 209 Setyaningsih, D. 148 Sirait, K.E. 251 Siregar, H.H. 1 Slamet, A.S 1 Soewardi, K. 34 Subiyantoro 243 Sukmawati, L. 148 Sulaeman, A. 28 Sumaryanto 189 Sunarti, T.C. 125, 157, 179, 218 Suparno, O. 11, 179 Suprihatin 11, 72, 97, 243 Suryadarma, P. 251 Suryani, A. 72, 200 Suwandhi, I. 200 Syamsu, K. 20, 125, 226 Tambunan, A.H. 235 Tethool, E.F. 137 Tiryana, T. 200 Utami, R. 53 Waningsih, M. 53 Warsiki, E. 166 Winarti, C. 218 Wulandari, N. 166 Yani, M. 166, 189 Yoyo, T. 114 Yuwono, A.S. 235